PENERAPAN FUZZY ASSOCIATIVE MEMORY UNTUK MENGUKUR TINGKAT KEPUASAN PELANGGAN TERHADAP PELAYANAN PADA TOKO KOPIMA: APPLICATION OF FUZZY ASSOCIATIVE MEMORY TO MEASURE THE LEVEL OF CUSTOMER SATISFACTION REGARDING SERVICE AT THE KOPIMA STORE - Nur Wakhidah; Ira Nurul Febriani (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2024)
One of the advantages of information technology in the field of business is that it can help in measuring the level of customer satisfaction. Because measuring customer satisfaction is an important element in providing better, more efficient and more effective services. KOPIMA stores, which is a student cooperative, is experiencing unstable sales problems, this is the result of customer dissatisfaction. There is a system used to measure the level of customer satisfaction with services at KOPIMA stores to find out what are the expectations of customer complaints and how to evaluate service at KOPIMA stores. To measure the level of customer satisfaction with services at KOPIMA stores, the Fuzzy Associative Memory (FAM) method is used. FAM is a flexible decision-making method, which is a fuzzy system that maps fuzzy sets to other fuzzy sets. The output obtained is a web-based system, with the results of the FAM method that can be implemented to calculate customer satisfaction into the rating category, namely 8% satisfied and 92% very satisfied in the November 2022 assessment and December 2022 assessment, namely 4% satisfied and 96% very satisfied . So it can be concluded, customer satisfaction has increased with the assessment criteria being very satisfied with the service at the KOPIMA store.